RADIATION DOSE OPTIMIZATION IN PEDIATRIC IMAGING: PRACTICES AND PERCEPTIONS AMONG SAUDI ARABIAN RADIOLOGISTS - Abdullah Saqer Mounir Alotaibi, Ayman Edrees Mohammed Bin Basheer, Bader Muflih Hlal Alotaibi, Fahad Abdulla Masfer AlOtaibi, Hamad Abdullah Saad Alotaibi, Ibrahim Saghir Ali Alissa, Saad Mansour Hassan Al Dosari, Tareq Abdullah Alwan Alqarni (Chelonian Research Foundation, 2024)
Radiation dose optimization is of paramount importance in pediatric medical imaging due tochildren's increased susceptibility to radiation-induced harm and their longer life expectancycompared to adults. This study aimed to comprehensively investigate the current practices andperceptions related to radiation dose optimization in pediatric imaging among radiologistspracticing in Saudi Arabia. An online survey was disseminated to radiologists across varioushealthcare institutions in the country, collecting data on their specific pediatric imaging protocols,dose reduction techniques employed, and perceived barriers to achieving optimal doseoptimization. The survey results reveal that while the majority of Saudi radiologists possess a goodunderstanding of the significance of dose optimization and implement certain dose reductionstrategies, there is still considerable room for improvement in their practices. The key areasidentified for enhancement include increasing the use of dose monitoring software, developing andimplementing standardized pediatric imaging protocols across institutions, providing morecomprehensive training for radiologists on optimization techniques, and fostering bettercommunication with referring physicians to ensure appropriate study selection and doseoptimization.Respondents identified several barriers to implementing optimal dose optimization, including thelack of pediatric-specific imaging protocols, time constraints in clinical practice, and concernsabout compromising diagnostic image quality. This study provides valuable insights into thecurrent state of radiation protection practices in pediatric imaging in Saudi Arabia and highlightspotential avenues for further optimizing radiation dose to ensure the safest and most effectiveimaging care for children.